Urban Horticulture Necessity of the Future - Shekhar Solankey, Shashank; Akhtar, Shirin; Isabel Luna Maldonado, Alejandro; Rodriguez-Fuentes, Humberto; Antonio Vidales Contreras, Juan; Mariana Márquez Reyes, Julia (IntechOpen, 2020)
Urban horticulture is a means of utilizing every little space available in cities amidst buildings and other constructions for growing plants. It utilizes this space to raise gardens that can be economically productive while contributing to environmental greening. It can boost food and ornamental plants production, provide job opportunities, promote green space development, waste recycling, and urban landscaping, and result in improved environment. This book covers a wide array of topics on this subject and constitutes a valuable reference guide for students, professors, researchers, builders, and horticulturists concerned with urban horticulture, city planning, biodiversity, and the sustainable development of horticultural resources.